New Materials: Natural Elements and the Body in Screendance - Vitaglione, Sylvie Michelle (The International Journal of Screendance, 2016)
This article explores the practice of shooting on location in screendance advocating for a practice that explores the concept of material specificity in order to create grounded conceptual works. In order to metaphorically and literally ground the dancing body, this article examines the crucial dichotomy between intervention in sites and integration of sites in order to understand exactly what stance screendance takes on its settings. In other words, what do artists take from the site and what do they bring to it? I begin by examining various definitions of site-specificity. By surveying theories and practices surrounding the artistic treatments of locations, my aim is to highlight the choreographic and cinematic techniques that connect the dancing body to the environment. I argue that through the use of natural elements these films articulate a version of site-specificity deeply connected to the materiality of each location rather than to its geography or history.